Synthesis and structural analysis of Mo/B periodical multilayer X-ray mirrors for beyond extreme ultraviolet optics. (15th January 2021) - Penkov, Oleksiy V.; Kopylets, Igor A.; Kondratenko, Valeriy V.; Khadem, Mahdi
Abstract: The synthesis and structural analysis of Mo/B periodical multilayer X-ray mirrors (PMMs) for beyond extreme ultraviolet (BEUV) optics was performed. The PMMs were deposited by a combination of pulsed DC and radio frequency (RF) magnetron sputtering. The structure was analyzed by high-resolution transmission electron microscopy, X-ray photoelectron spectroscopy, and grazing incidence X-ray reflectometry. The formation of 0.35 nm-thick interlayers comprised of a mixture of molybdenum borides was observed at the Mo/B interfaces. Furthermore, a low interface roughness of 0.3–0.4 nm was reported. The temperature of the substrate increased due to the increase in the sputtering power. This resulted in an increase in the thickness of the interlayers and the interface roughness; subsequently, the optical properties of the PMM deteriorated. Theoretical calculations were performed based on the real structure of the PMM to predict the reflectivity at a working wavelength of 6.7 nm. The reflectivity of approximately 53% was two times higher than that of the conventional B4 C-based BEUV mirrors. Based on our study results, it can be concluded that the as-synthesized PMMs will perform better than the traditional mirrors and can be effectively used for the development of the next generation of BEUV lithography. Graphical abstract: Unlabelled Image Highlights: Amorphous nanolayers of B and Mo are separated by 0.4–0.45 nm thick interlayers consisted of MoB and MoB2 . Increasing the power of B magnetron from 280 to 330 W causes the interlayers' growth to 0.5–0.6 nm. The predicted reflectivity of Mo/B multilayer mirror at the wavelength of 6.7 nm is ~53%.